Pengaruh Ketebalan Media Budidaya Cacing Sutra (Tubifex sp.) Menggunakan Lumpur Limbah Budidaya Lele - Dindin Suryadin; Senny Helmiati; Rustadi Rustadi (Universitas Gadjah Mada, 2017)
This research aims to know the influence of the thickness of catfish culture waste on silk worm (Tubifex sp.) biomass. The research was conducted with culturing Tubifex sp. in different thickness media of the waste as treatments. The treatments consist of the waste 2, 4, 8 and 12 cm thickness of medium with 6 cm depth. The stock densities 150 g/m3 with average weight 0.0062+0.00032 g. The parameter that analyzed is biomass and population of Tubifex sp.. Data analyzed by analysis of variance and posthoc test is Duncan’s Multiple Range Test. The result shows that diversification of medium thickness gives the real influence (P<0.05) to Tubifex sp. biomass. The highest biomass 1745.14±143.77 g/m3 and population 233,848.46±19265.61 ind./m3 on the treatment with 8 cm thickness. The relationship between treatment and biomass production of Tubifex sp. is quadratic relationship with y = -30.405x2 + 552.18x – 823.55. The optimum thickness of medium that results maximum biomass production is 9.1 cm.